2018
DOI: 10.1007/s12020-018-1550-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperirisinemia is independently associated with subclinical hypothyroidism: correlations with cardiometabolic biomarkers and risk factors

Abstract: Irisin may represent an adipo-myokine counterbalancing a potential, gradual deterioration of lipid metabolism and insulin sensitivity in SH as well as reflecting a protective compensatory mechanism against oxidative muscle and thyroid cell stress. More mechanistic and prospective studies shedding light on the pathogenetic role of irisin in SH are needed to confirm and extend these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 42 publications
3
41
0
3
Order By: Relevance
“…Stratigou and cols. suggested that irisin might represent an adipo-myokine counterbalancing the deterioration of lipid metabolism and insulin sensitivity in SCH as well as reflecting a protective compensatory mechanism against oxidative muscle and thyroid cell stress (15). In our study irisin levels in subclinical hypothyroid patients were similar to healthy controls.…”
Section: Adipokines In Subclinical Hypothyroidismsupporting
confidence: 71%
See 2 more Smart Citations
“…Stratigou and cols. suggested that irisin might represent an adipo-myokine counterbalancing the deterioration of lipid metabolism and insulin sensitivity in SCH as well as reflecting a protective compensatory mechanism against oxidative muscle and thyroid cell stress (15). In our study irisin levels in subclinical hypothyroid patients were similar to healthy controls.…”
Section: Adipokines In Subclinical Hypothyroidismsupporting
confidence: 71%
“…Irisin was previously studied in patients with SCH (14,15), but only Stratigou and cols. evaluated serum irisin levels after being euthyroid with levothyroxine treatment (15). Apelin was studied in patients with SCH (10,13), however it was also not evaluated after becoming euthyroid.…”
Section: Adipokines In Subclinical Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text evaluation excluded 158 articles. Thus, 29 articles were included in the final meta-analysis ( 23 27 , 40 63 ). Among them, 10 studies were RCTs including 1,637 participants ( 40 49 ) and the other 19 studies were prospective follow-up studies including 571 participants ( 23 27 , 50 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggested that LT4 therapy could offer benefits for SCH patients through decreasing TSH level, such as the lipid-lowering effect ( 21 , 22 ). Findings from several studies revealed that LT4 therapy reduced blood pressure in SCH patients ( 23 25 ), but other studies did not support it ( 26 , 27 ). Therefore, there is still no consensus regarding the effect of LT4 therapy on blood pressure in SCH patients.…”
Section: Introductionmentioning
confidence: 99%